Determinants of Smallholder Farmers Participation in Community-Based Onion Seed Producing and Marketing Cooperatives in Northwest Ethiopia - Wondimagegnhu, Boneberu Assefa; Heyi, Girma Eshetu (Journal of Agricultural Extension Management, 2019)
Onion seeds are mainly supplied by community based seed production and marketing cooperatives in Ethiopia. The problem of seed marketing which was faced by the onion seed producer and marketing cooperatives of Mecha district of Amhara regional state is the major reason for undertaking this study. The study analyzes the main factors for members’ participation in their cooperatives. This objective serves as an indicator for the general performance of the cooperatives in running the seed business. The research used descriptive statistics and binary logistic regression model to assess members’ socio-economic, demographic and institutional factors determining members’ participation in cooperatives and describes seed quality status. A Semi-structured questionnaire was employed to collect primary data. A total of 120 members were randomly selected from three cooperatives in February, 2018. The study indicated that the cooperatives have been weak in making profit from the seed marketing due to their poor involvement in onion seed distribution and supply of other inputs. The findings show that there exists significant difference between active and inactive members of the cooperatives in terms of land ownership, duration of membership, information and training access, dividend obtained, satisfaction on management and communication channels used. The logistic regression result indicated that land holding, access to training for members and communication channel used were significant in determining the level of members’ participation. The cooperatives should improve their scope and performance so as to enable members to engage more in production and marketing of seeds and enhance their participation.